Comparative efficacy of short-acting and long-acting quinidine for maintenance of sinus rhythm after electrical conversion of atrial fibrillation. Issue 4 (April 1976) - Normand, J P; Legendre, M; Kahn, J C; Bourdarias, J P; Mathivat, A
Abstract : Forty patients with chronic atrial fibrillation, apparently unrelated to any overt heart disease, were randomly allocated to two groups after restoration of sinus rhythm by direct current shock. The patients in group A were given 4 daily doses of quinidine polygalacturonate, while those in group B were given 2 daily doses of a long-acting quinidine preparation, quinidine arabogalactan sulphate. The percentage of early relapses (within the first month following DC shock) was not significantly different in the two groups: 44-4% in group A and 35% in group B (P greater than 0-50). On the other hand, there were fewer late relapses with long-acting quinidine. After 18 months of treatment, 27-8% of patient in group A remained in sinus rhythm, compared with 61% in group B (P less than 0-05). The average amount of quinidine actually ingested by the patients in group A was smaller than that in group B. However, this could not entirely account for the difference observed in the incidence of relapse since with short-acting quinidine the proportion of patients remaining in sinu rhythm was similar whether the dose was decreased or not. The incidence of gastrointestinal side-effects was the same in the two groups and there were no seriou complications that could be attributed to treatment. It is concluded that long-acting quinidine preparations are more effective than conventional quinidine in preventing late relapses of atrial fibrillation.